Enhanced Antimicrobial Action of Chlorhexidine Loaded in Shellac Nanoparticles with Cationic Surface Functionality - Saba S. M. Al-Obaidy; Gillian M. Greenway; Vesselin N. Paunov (MDPI AG, 2021)
We report on an active nanocarrier for chlorhexidine (CHX) based on sterically stabilized shellac nanoparticles (NPs) with dual surface functionalization, which greatly enhances the antimicrobial action of CHX. The fabrication process for the CHX nanocarrier is based on pH-induced co-precipitation of CHX-DG from an aqueous solution of ammonium shellac and Poloxamer 407 (P407), which serves as a steric stabilizing agent. This is followed by further surface modification with octadecyl trimethyl ammonium bromide (ODTAB) through a solvent change to yield cationic surface functionality. In this study, we assessed the encapsulation efficiency and release kinetics of the novel nanocarrier for CHX. We further examined the antimicrobial effects of the CHX nanocarriers and their individual components in order to gain better insight into how they work, to improve their design and to explore the impacts of their dual functionalization. The antimicrobial actions of CHX loaded in shellac NPs were examined on three different proxy microorganisms: a Gram-negative bacterium (E. coli), a yeast (S. cerevisiae) and a microalgae (C. reinhardtii). The antimicrobial actions of free CHX and CHX-loaded shellac NPs were compared over the same CHX concentration range. We found that the non-coated shellac NPs loaded with CHX showed inferior action compared with free CHX due to their negative surface charge; however, the ODTAB-coated, CHX-loaded shellac NPs strongly amplified the antimicrobial action of the CHX for the tested microorganisms. The enhancement of the CHX antimicrobial action was thought to be due to the increased electrostatic adhesion between the cationic surface of the ODTAB-coated, CHX-loaded shellac NPs and the anionic surface of the cell walls of the microorganisms, ensuring direct delivery of CHX with a high concentration locally on the cell membrane. The novel CHX nanocarriers with enhanced antimicrobial action may potentially find applications in dentistry for the development of more efficient formulations against conditions such as gingivitis, periodontitis and other oral infections, as well as enabling formulations to have lower CHX concentrations.